Bevacizumab for advanced cervical cancer: patient-reported outcomes of a randomised, phase 3 trial (NRG Oncology–Gynecologic Oncology Group protocol 240). Issue 3 (March 2015) - Penson, Richard T; Huang, Helen Q; Wenzel, Lari B; Monk, Bradley J; Stockman, Sharon; Long, Harry J; Ramondetta, Lois M; Landrum, Lisa M; Oaknin, Ana; Reid, Thomas J A; Leitao, Mario M; Method, Michael; et al.
Summary: Background: GOG 240 was a practice-changing randomised phase 3 trial that concluded that chemotherapy plus bevacizumab for advanced cervical cancer significantly improves overall and progression-free survival, and the proportion of patients achieving an overall objective response, compared with chemotherapy alone. In this study, we aimed to analyse patient-reported outcomes in GOG 240. Methods: Eligible adult participants (aged ≥18 years) had primary stage IVB or recurrent or persistent carcinoma of the cervix with measurable disease and GOG performance status of 0–1. Participants were randomly assigned by web-based permuted block randomisation (block size 4) in a 1:1:1:1 ratio to the four treatment groups: cisplatin (50 mg/m 2 intravenously on day 1 or 2 of the treatment cycle) and paclitaxel (135 mg/m 2 intravenously over 24 h or 175 mg/m 2 intravenously over 3 h on day 1), with or without bevacizumab (15 mg/kg intravenously on day 1 or 2), or paclitaxel (175 mg/m 2 over 3 h on day 1) and topotecan (0·75 mg/m 2 for 30 min on days 1–3) with or without bevacizumab (15 mg/kg intravenously on day 1). Treatment assignment was concealed at randomisation (everyone was masked to treatment assignment, achieved by the use of a computer encrypted numbering system at the National Cancer Institute) and became open-label when each patient was registered to the trial. Treatment cycles were repeated every 21 days until disease progression or unacceptable toxicity, whichever occurred first. The coprimary endpoints of the trial were overall survival and safety; the primary quality-of-life endpoint was the score on the Functional Assessment of Cancer Therapy-Cervix Trial Outcome Index (FACT-Cx TOI). For our analysis of patient-reported outcomes, participants were assessed before treatment cycles 1, 2, and 5, and at 6 and 9 months after the start of cycle 1, with the FACT-Cx TOI, items from the FACT-GOG-Neurotoxicity subscale, and a worst pain item from the Brief Pain Inventory. All patients who completed baseline quality-of-life assessments and at least one further follow-up assessment were evaluable for quality-of-life outcomes. This study is registered withClinicalTrials.gov, numberNCT00803062 . Findings: Between April 6, 2009, and Jan 3, 2012, a total of 452 patients were enrolled in the trial, of whom 390 completed baseline quality-of-life assessment and at least one further assessment and were therefore evaluable for quality-of-life outcomes. In these patients, patient-reported outcome completion declined from 426 (94%) of 452 (at baseline) to 193 (63%) of 307 (9 months post-cycle 1), but completion rates did not differ significantly between treatment regimens (p=0·78). The baseline FACT-Cx TOI scores did not differ significantly between patients who received bevacizumab versus those who did not (p=0·27). Compared with patients who received chemotherapy alone, patients who received chemotherapy plus bevacizumab reported FACT-Cx TOI scores that were an average of 1·2 points lower (98·75% CI −4·1 to 1·7; p=0·30). Interpretation: Improvements in overall survival and progression-free survival attributed to the incorporation of bevacizumab into the treatment of advanced cervical cancer were not accompanied by any significant deterioration in health-related quality of life. Patients responding to anti-angiogenesis therapy who maintain an acceptable quality of life could be suitable at progression for treatment with other novel therapies that might confer additional benefit. Funding: National Institutes of Health.